Producing Digital Models of Elevations (DEMs) using Surfer 16 - Mahdi Ali, Amal; Sameer Sadiq , Noor; Khalid Jasim, Luma; Abad AL-Jabbar Kasim, Rokaya (Iraqi Journal of Science, 2026)
Digital Models of Elevations (DEMs) Using Surfer 16, which are interpolated to create three-dimensional controls for the entire terrain, are typically used in visualization of geospatial entities. The interpolation method used determines how accurate the resulting terrain model will be, hence it is necessary to compare the effectiveness of various approaches in this situation. Numerous generic interpolation techniques, using inverse distance to a power, triangulation as with linear interpolation, the nearest neighbor, and kriging, have been studied. These interpolation techniques produced DEMs. With the aid of SURFER software 16, the primary goal of this effort was to introduce the DEM using a spatial interpolation method and to present comparisons and outcomes. To create digital elevation models, the SURFER software offers four interpolation techniques. The results demonstrated that the DEMs’ accuracy was within computed limits for variance, root mean square error, and coefficient of determination (R2).